A Multicenter Randomized Trial Assessing ZENFlow Carrier-Free Drug-Coated Balloon for the Treatment of Femoropopliteal Artery Lesions - Ni, Leng; Ye, Wei; Zhang, Lan; Jin, Xing; Shu, Chang; Jiang, Jin-song; Yang, Mu; Wu, Dan-ming; Li, Ming; Yu, Guan-feng; Yang, Jun; Huang, Jian-hua; et al. (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds and Objectives: Drug-coated balloons (DCBs) have shown promising benefits in improving the outcomes for patients with peripheral artery disease. Several randomized clinical trials have reported that paclitaxel-coated balloon significantly reduce the rates of restenosis and the need for reintervention in comparison with regular balloon angioplasty. Due to the differences in excipients, paclitaxel dose, and coating techniques, variable clinical outcomes have been observed with different DCBs. In this study, we aimed to evaluate the safety and efficacy of a novel ZENFlow carrier-free DCB in the treatment of femoropopliteal artery occlusive disease. Methods: In this randomized controlled trial conducted at 15 sites, 192 patients with Rutherford class 3–5 were randomly assigned into two groups: drug-coated balloon group and percutaneous transluminal angioplasty group. The primary endpoint was a late lumen loss at 6 months based on blinded angiographic core laboratory evaluations, and the secondary endpoints included primary patency rate, binary restenosis, clinically driven target lesion revascularization, ankle-brachial index, Rutherford class change, and major adverse events. Results: In this multicenter trial, 93 patients received DCB angioplasty, whereas 99 patients underwent regular balloon angioplasty. The late lumen loss at 6-month follow-up was 0.50±0.82 and 1.69±0.87 mm in the drug-coated balloon and percutaneous transluminal angioplasty groups, respectively (p<0.001). During the 12-month follow-up period, the drug-coated balloon group showed a significantly higher primary patency rate (54% vs. 31.3%, p=0.009) and markedly lower rates of target vessel restenosis (22.1% vs. 64.3%, p<0.001) and clinically driven target lesion revascularization rate (5.4% vs. 19.2%, p=0.006) than the percutaneous transluminal angioplasty group. Compared with the percutaneous transluminal angioplasty group, the drug-coated balloon group had significant improvements in the ankle-brachial index and Rutherford class. The all-cause mortality rate was comparable, and no device-related deaths occurred in either groups. Conclusions: Balloon angioplasty using a ZENFlow carrier-free drug-coated balloon is a safe and effective treatment method for femoropopliteal artery lesions. This novel drug-coated balloon catheter achieved satisfactory early and 1-year outcomes in this trial. ClinicalTrials.gov Identifier: NCT03844724.